Establishing an infection control accreditation programme to control infection - Parker, Julie (International Journal of Infection Control, 2008)
Faced with increasing scrutiny from the Healthcare Commission, the Department of Health and the Strategic Health Authority, as well as a challenging Methicillin Resistant Staphylococcus aureus (MRSA) bacteraemias reduction target, the infection prevention and control team (IPCT) developed an accreditation programme designed to devolve ownership of infection prevention and control to clinical areas. The programme was devised as a quality improvement programme to improve patient care and has helped to ensure that evidence-based practice is embedded in everyday clinical activities within all clinical areas. The roll out of the programme started in high risk, medium risk and then low risk areas in the hospital and has contributed to significantly improved compliance with infection control policies, procedures and guidelines and a reduction in the MRSA bacteraemia rate by 39% in 2007/2008. Hospital acquired MRSA infections (detected from first isolates) also reduced by approximately 60% in 2007/2008. However, Clostridium difficile rates in 2007/2008 remained comparable with the previous year until early 2008, although a significant reduction is now evident.